Preparation Characterization and Study Thermal Properties of New Aromatie Polyester Based on Di Hydroxyl Monomers With 4,4-Azo Di Benzoic Acid Maleic Acid and Phthalic Acid (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
In this work series of new aromatic Polyesters were synthesized by polycondensation of various aromatic monomers  di hydroxyl .this monomers containing on pyridine heterocyclic ring ,aliphatic methylene linkage and 4,4-Azo di benzoic acid (BCHPBM, BHPFM,FBHP,CPBHP) with Acids(4,4Azo di benzoic acid, phthalic acid and Maleic acid) using dibutyltine dilaurate as Catalyst .all polyesters(P.E1-P.E4)containing pyridine heterocyclic ring, aliphatic methylene linkage, and Azo group. The yield of Polyesters varies from 75-88%. All of  these  new  aromatic polyester  show very good  solubility in common organic  solvents, such as (pyridine, CHCl3,  CH2Cl2 , NaOH, H2SO4, HNO3, acetone, benzene, DMF, DMSO, THF) without need for heating. Thermal stability of polyesters was studied using thermo gravimetric analysis (TGA). Monomers and polyesters characterized by spectrosticcopyFT-IRand1HNMR.